Breaking Coaching's Rules: Transforming the Body, Sport, and Performance. (June 2020) - Mills, Joseph; Denison, Jim; Gearity, Brian
"Who knew that doing the wrong things could make everything so right?" There can be little doubt that sports' dominant bioscientific articulation of the athletic body exerts a strong influence on coaches. Yet, on closer examination, this articulation and the practices it produces are not as straightforward as most coaches and scholars assume. Within the sociocultural study of coaching, scholars have drawn on Michel Foucault's disciplinary framework to analyze many unseen problems and unintended consequences associated with coaches' normal or everyday (bioscientific) practices. However, one significant aspect of Foucault's theoretical framework that has received less attention from coaching scholars is how power and discourse work together to produce several coaching "truths." To address this gap, in this article, we analyze the first author's experiences as an international middle-distance runner by showing and telling what problems and constraints are produced when coaches, and by association their athletes, defer to a dominant bioscientific articulation of the athletic body in their training. We conclude by discussing the transformative possibilities when these "truths" are broken.